A Model-Driven Analysis of Mimblewimble Security Properties and its Protocol Implementations - Silveira, Adrián (2023)
Mimblewimble is a privacy-oriented cryptocurrency technology that provides security and scalability properties that distinguish it from other protocols. Mimblewimble’s cryptographic approach is based on Elliptic Curve Cryptography which allows verifying a transaction without revealing any information about the transactional amount or the parties involved. Mimblewimble combines Confidential transactions, CoinJoin, and cut-through to achieve a higher level of privacy, security, and scalability. In this work, we present and discuss these security properties and outline the basis of a model-driven verification approach to address the certification of the correctness of the protocol implementations. In particular, we propose an idealized model that is key in the described verification process. Then, we identify and precisely state the conditions for our model to ensure the verification of relevant security properties of Mimblewimble. In addition, we analyze the Grin and Beam implementations of Mimblewimble in their current state of development. We present detailed connections between our model and their implementations regarding the Mimblewimble structure and its security properties.